IMPEDING FACTORS FACED BY THE ENGLISH TEACHERS IN IMPLEMENTING TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE FRAMEWORK IN TEACHING AT SENIOR HIGH SCHOOLS IN BULELENG SUB-DISTRICT - Widyanti, N.W.; Santosa, M.H.; Utami, I.G.A.L.P. (Universitas Pendidikan Ganesha, 2019)
This study was qualitative research design focused on investigating the impeding factors faced by the English teachers in implementing technological pedagogical content knowledge framework in teaching. This study was investigated the interview using voice recorder (handphone) and took 9 English teachers in order to investigate the impeding factors faced by the teachers in implementing technological pedagogical content knowledge framework. The result of the interview data processed by using four analysis from Miles and Huberman (1994), namely data collection, data reduction, data display and conclusion drawing/verification. The result showed that there were two impeding factors faced by the English teachers at senior high schools in Buleleng sub-district in implementing technological pedagogical content knowledge framework in teaching, they were facilities and students’ attitude. However, those could be solved by the teachers through does not using the facilities together in the same time and make the regulation for the students when implementing technology.